Transport through leaked Majorana modes in quantum dots and adatoms - Penteado, Poliana Heiffig (2013)
We investigate quantum resonant transport in two different systems: (i) a ferromagnetic Scanning Tunneling Microscope (STM) tip coupled to an adatom (interacting) on a host surface (metallic or semiconductor), and (ii) a quantum dot connected to source and drain leads and side-coupled to a superconducting nanowire sustaining Majorana zero modes (Kitaev chain). Both problems are studied within the Green’s functions approach, which allows us to determine the transport properties of the system. In the first setup, due to the ferromagnetic and nonmagnetic ‘natures’ of the tip and host, respectively, it is possible to obtain the spin-diode effect, which occurs only in the singly occupied regime. In addition, because of the presence of the adsorbed atom on the surface, Friedel oscillations are observed in the current. The second system differs from the first mainly because it is spinless and there is no Coloumb interaction. Interestingly, we find that the Majorana mode of the wire leaks into the dot thus giving rise to a Majorana (zero mode) resonance in the dot, pinned to the Fermi level of the leads. Surprisingly, this resonance occurs even when the gate-controlled dot level is far above or far below the Fermi level of the leads. We study three possible experimental scenarios to probe unambigoulsy this Majorana mode in wires via these leaked/pinned modes.